Trait preferences of sorghum and pearl millet value chain actors in Mali and Burkina Faso: a case for gender- responsive and demand-driven breeding - Yila, Jummai O.; Sylla, Almamy; Traore, Sekou; Sawadogo-Compaoré, Eveline M. F. W. (Frontiers in Sustainable Food Systems, 2024)
Sorghum and pearl millet have adapted to the socioecological environment in the dryland of West Africa and have been the staple crops for many years. Engaging key stakeholders and improving the sorghum and pearl millet breeding process is essential to addressing the evolving demands of end-users and environmental conditions. Unlike most trait preference studies focusing on men and women farmers’ trait choices, we examined sorghum and pearl millet key value chain actors (VCA), including producers, processors, traders, and consumers. We identified their preferred traits of varieties that need to be mainstreamed into the breeding pipelines. Drawing on the past efforts and experiences of the sorghum and pearl millet breeding programs from the last 30 years, the study was designed to integrate gender equality in sorghum and pearl millet breeding decisions and traits prioritization in West Africa. This process was implemented in phases, leading to the drafting of gender-responsive and client-oriented product profiles. The paper elicited an understanding of how the roles and interests of sorghum and pearl millet VCA influence their varietal choice and adoption decisions. The study found both differences and similarities in the trait preferences of the men and women VCA. Most women, mainly in the production and processing nodes, prefer varieties with specific food and grain quality traits, while men prioritize grain yield and biotic stress resistance traits. Even though both men’s and women’s varietal choices align with their roles in production and consumption, grain yield was commonly desired across gender, crop, and value chain segments. The findings revealed that the gendered interest of actors in the crops’ value chain determines their choice of variety. Gender responsiveness requires identifying and understanding the needs and choices of the sorghum and millet VCA and mainstreaming these into the breeding pipeline. The approach employed in the study elicits the understanding, roles, and interests of the various actors and how these factors influence men’s and women’s decisions to adopt a crop variety. All major stakeholders should co-develop product profiles for the variety being developed to enable co-ownership, increase adoption, and improve gender equity in agricultural technology development and deployment.